Study of the Environmental Friendliness and Financial Belat in the Waters of Siak River Benayah Village Siak Regency Riau Province - Setiawan, Arief; Bustari, Bustari; Brown, Arthur (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2023)
The waters of the Siak River in Benayah Village have several fishing gears used in fishing activities. One of the fishing gears used is belat. The belat is a type of trap and is included in the classification of other trapping devices (other traps). The purpose of this study was to determine the construction of fishing gear in general, fishing operations, and the level of environmental friendliness and the feasibility of the belat fishing business. This research was carried out in December 2022 in the waters of the Siak River. The method used in this research is the survey method. The results of the FAO withdrawal study (1995) showed that the belat in Benayah Village was classified as a very environmentally friendly fishing technology. The results of the analysis of the business of fishing for belat known (NPV) with a prediction of 10 years show that the business of catching maggots achieves a return of capital in the 1st year of IDR 1,995,283